High‐throughput SNP‐genotyping analysis of the relationships among Ponto‐Caspian sturgeon species. Issue 8 (1st July 2013) - Rastorguev, Sergey M.; Nedoluzhko, Artem V.; Mazur, Alexander M.; Gruzdeva, Natalia M.; Volkov, Alexander A.; Barmintseva, Anna E.; Mugue, Nikolai S.; Prokhortchouk, Egor B.
Abstract Legally certified sturgeon fisheries require population protection and conservation methods, including DNA tests to identify the source of valuable sturgeon roe. However, the available genetic data are insufficient to distinguish between different sturgeon populations, and are even unable to distinguish between some species. We performed high‐throughput single‐nucleotide polymorphism (SNP)‐genotyping analysis on different populations of Russian (Acipenser gueldenstaedtii), Persian (A. persicus), and Siberian (A. baerii) sturgeon species from the Caspian Sea region (Volga and Ural Rivers), the Azov Sea, and two Siberian rivers. We found that Russian sturgeons from the Volga and Ural Rivers were essentially indistinguishable, but they differed from Russian sturgeons in the Azov Sea, and from Persian and Siberian sturgeons. We identified eight SNPs that were sufficient to distinguish these sturgeon populations with 80% confidence, and allowed the development of markers to distinguish sturgeon species. Finally, on the basis of our SNP data, we propose that the A. baerii‐like mitochondrial DNA found in some Russian sturgeons from the Caspian Sea arose via an introgression event during the Pleistocene glaciation.